Comprehensive Management of Peripartum Cardiomyopathy with Acute Renal Failure: From Prepartum to Renal Replacement Therapy – A Case Report - Niazta, Nisa Amnifolia; Putri, Valerinna Yogibuana Swastika (Ikatan Dokter Indonesia Wilayah Jawa Timur, 2025)
Introduction: Peripartum cardiomyopathy (PPCM) is a rare but potentially serious that poses significant diagnostic and therapeutic challenges, particularly in previously healthy women. We report a complex case of severe PPCM in a primigravida patient who needed intensive multidisciplinary care due to respiratory failure and acute renal failure. Case Presentation: A 21-year-old primigravida in 34 weeks of gestation presented with progressive dyspnea and signs of acute heart failure. Despite an unremarkable medical history, she exhibited severe left ventricular dysfunction (LVEF of 28%), cardiomegaly, and pulmonary congestion. Rapid deterioration necessitated urgent caesarean delivery under general anesthesia due to maternal and fetal distress. Postoperatively, the patient developed cardiogenic shock and acute kidney injury (AKI) necessitating vasopressor and continuous renal replacement therapy (CRRT). Intensive heart failure management, including bromocriptine therapy and guideline-directed medical treatment, led to gradual hemodynamic stabilization. She was successfully weaned off mechanical ventilation and CRRT within days, ultimately being discharged after 12 days of treatment with improved cardiac function. Conclusion: This case underscores the unpredictable nature and rapid progression of PPCM, even in the absence of traditional risk factors. Early recognition, prompt multidisciplinary intervention, and individualized therapy are critical to improving maternal and neonatal outcomes.